Identifying patient perceived values during outpatient encounters: an empirical study from Chinese public hospitals - Sha Liu; Yinhuan Hu; Chuntao Lu; Dehe Li; Zemiao Zhang (BMC, 2023)
Abstract Background Focusing on patients' perceived values is essential for patient-centered health care. Only by identifying the patient's preferred values can we better meet their needs and provide them with valuable medical services. This study aimed to construct and validate a research model to obtain an overall quantification of patient value during outpatient encounters. Methods The development of the research model was based on the reviewed literature, and an initial theoretical framework was formed by an expert panel discussion. A scale questionnaire for all the items was adapted from previous research related to patient value, verified using a presurvey, and thus used for data collection for this study. The structural equation model was used to determine and evaluate the research model of the values patients perceived during outpatient encounters. Results 572 eligible respondents who completed outpatient visits from a typical public hospital in China participated in this study from November 2020 to February 2021. We constructed the patient perceived value (PPV) model to identify core values, which includes eight dimensions and 29 items in terms of functional value (installation, efficiency, price, service quality), emotional value (interactive, control), and social value (accessibility, image) from two subgroups of patient value outside and in the outpatient visit process. Cronbach's alpha for the whole model was 0.950. The confirmatory factor analysis showed that the PPV model fits well, with a correlation of 0.83 between the two subgroups. Conclusion It is essential to recognize the values based on patients' perceptions and experiences throughout the entire visit process. Our findings offer targeted insights for healthcare administrators, enabling them to holistically optimize outpatient service processes and continually enhance the quality of outpatient medical services from the patient's perspective.